Revisiting the circumscription of Chusquea anelythra (Poaceae–Bambusoideae–Bambuseae): lectotypification, redescription, geographic distribution, and conservation status - Vidal, Kaio Vinicius De A.; Welker, Cassiano A. Dorneles; Silva, Alaísma Pereira Da; Santos-Gonçalves, Ana Paula; Clark, Lynn G.; Oliveira, Reyjane P. (Phytotaxa, 2021)
With 193 described species, Chusquea is the most diverse bamboo genus in the Neotropical region. Brazil, with 48 accepted species and 44 of them endemic, is one of its major centers of diversity. Among the Brazilian species, C. anelythra was only superficially characterized in its original publication almost 200 years ago, without a clear definition of its type-material, description of culm leaves, or comments on its geographic distribution or related species. As the absence of such information has greatly complicated the taxonomic delimitation of C. anelythra, the major aim of this paper is to clarify the identity of this species based on fieldwork and herbarium investigation, providing an emended description, illustrations, and photos of this species. We also designate a lectotype for the name C. anelythra, and provide a morphological comparison with two similar members of the C. meyeriana informal group. Geographic distribution and conservation status are also updated for this species.